Rough Guides and Carbon Ruins: The Role of Sf (Studies) in the (Re)Construction of Decarbonized Futures. Issue 1 (1st April 2023) - Raven, Paul Graham
Abstract : This essay asks scholars to overcome the disciplinary divides between the humanities on the one side and the social sciences on the other in order to imagine hopeful future alternatives to petromodernity. This collaboration can only be effective if both sides are open to it, which is why I suggest leveraging speculative design as a means to bridging the disciplines. Speculative design not only unlocks avenues for generating impact outside academia that funding institutions demand but also allows for meta-theoretical self-reflection. I present two examples of such design fictions: a vision of a largely decarbonized European city in the mid-2040s and a future museum in which traces of late twentieth-/early twenty-first-century oil culture are on display. These two examples showcase how methods and theories from the arts and humanities can be applied in "the real world" to reconfigure imaginaries. This article was published open access under a CC BY licence: https://creativecommons.org/licences/by/4.0 .